2012
DOI: 10.1152/ajpcell.00324.2011
|View full text |Cite
|
Sign up to set email alerts
|

Proton block of the pore underlies the inhibition of hERG cardiac K+ channels during acidosis

Abstract: Van Slyke AC, Cheng YM, Mafi P, Allard CR, Hull CM, Shi YP, Claydon TW. Proton block of the pore underlies the inhibition of hERG cardiac K ϩ channels during acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…The Relaxed State of the Voltage Sensor Is Destabilized by Extracellular Protons hERG channel deactivation kinetics are sensitive to changes in the extracellular proton concentration and numerous studies have shown that acidosis accelerates deactivation rate (Anumonwo et al, 1999;Bérubé et al, 1999;Jiang et al, 1999;Terai et al, 2000;Bett and Rasmusson, 2003;Du et al, 2010;Zhou and Bett, 2010;Du et al, 2011;Van Slyke et al, 2012;Shi et al, 2014;Shi et al, 2019). pH reductions within the physiological range (as low as pH 6.5) accelerated both the fast and the slow components of deactivation with a pKa of~6.8 (Bett and Rasmusson, 2003;Shi et al, 2019) with little effect channel conductance, and other voltage-dependent gating parameters (Jiang et al, 1999;Bett and Rasmusson, 2003;Shi et al, 2019).…”
Section: Targeted Modulation Of Herg Voltage Sensor Relaxationmentioning
confidence: 99%
“…The Relaxed State of the Voltage Sensor Is Destabilized by Extracellular Protons hERG channel deactivation kinetics are sensitive to changes in the extracellular proton concentration and numerous studies have shown that acidosis accelerates deactivation rate (Anumonwo et al, 1999;Bérubé et al, 1999;Jiang et al, 1999;Terai et al, 2000;Bett and Rasmusson, 2003;Du et al, 2010;Zhou and Bett, 2010;Du et al, 2011;Van Slyke et al, 2012;Shi et al, 2014;Shi et al, 2019). pH reductions within the physiological range (as low as pH 6.5) accelerated both the fast and the slow components of deactivation with a pKa of~6.8 (Bett and Rasmusson, 2003;Shi et al, 2019) with little effect channel conductance, and other voltage-dependent gating parameters (Jiang et al, 1999;Bett and Rasmusson, 2003;Shi et al, 2019).…”
Section: Targeted Modulation Of Herg Voltage Sensor Relaxationmentioning
confidence: 99%
“…Slowing of activation gating by external protons was reported for Kv10.1 (Terlau et al, 1996) and Kv11.1 (Zhou and Bett, 2010) but not Kv12.1 (Shi et al, 1998). Extracellular pH also accelerates Kv11.1 deactivation (Anumonwo et al, 1999; Jiang et al, 1999) and decreases its open channel conductance via proton pore block (Van Slyke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of pH i on ion channel function have been suggested to play a role in vascular cells . In the context of the present study, it is relevant to note that most K + channels are inhibited at low rather than high pH i (Xu et al 1996;Schubert et al 2001;Mao et al 2003;Van Slyke et al 2012) and hence inhibition of IK and SK channels is an unlikely explanation for the reduced EDH. This conclusion is further supported by our observation that the EC hyperpolarisation upon acetylcholine stimulation was not significantly affected by CO 2 /HCO 3 − -free conditions.…”
Section: Figure 8 Intercellular Dye Coupling (Propidium Iodide) Is Amentioning
confidence: 82%
“…2001; Mao et al . 2003; Van Slyke et al . 2012) and hence inhibition of IK and SK channels is an unlikely explanation for the reduced EDH.…”
Section: Discussionmentioning
confidence: 99%